COVID-19 and parents of children with epilepsy: Experiences and positive changes - Koliouli, Flora; Andrianakou, Marianna (Frontiers in Public Health, 2023)
Introduction The aim of this study is to explore the ways that parents with children or adolescents with epilepsy (CAWE) experienced the restrictive measures, as well as the stressors and challenges that they had to face. Methods We employed an experiential approach and fifteen Greek-speaking parents answered to an in-depth semi-structured interview, during the second lockdown period. Data were analyzed through the Thematic Analysis (TA). Results The emerging themes were the challenges encountered in terms of medical monitoring, the “stay-home” impact on their everyday lives as a family, their psycho-emotional responses. More specifically, parents identified the irregular doctor appointments and their struggle to access the hospital services as the most important challenges. Moreover, parents reported that the “stay-home” impact has disrupted their children's daily routines among others. Finally, parents highlighted their emotional strain and worries experienced during the lockdown along with the positive changes that occurred.